Studying the interaction of neutrophils and glaesserella parasuis indicates a serotype independent benefit from degradation of NETs - Bonilla, Marta C. (2022)
Glaesserella (G.) parasuis is one of the most important porcine pathogens causing Glaesser’s disease. Neutrophil granulocytes are the major counteracting cell type of the innate immune system, which contribute to the host defense by phagocytosis or the formation of neutrophil extracellular traps (NETs). Recently, NET-formation has been shown to facilitate the survival of bacteria from the Pasteurellaceae family. However, the interaction of NETs and G. parasuis is unclear so far. In this study, we investigated the interplay of three G. parasuis serotypes with porcine neutrophils. The production of reactive oxygen species by neutrophils after G. parasuis infection varied slightly among the serotypes but was generally low and not significantly influenced by the serotypes. Interestingly, we detected that independent of the serotype of G. parasuis, NET formation in neutrophils was induced to a small but significant extent. This phenomenon occurred despite the ability of G. parasuis to release nucleases, which can degrade NETs. Furthermore, the growth of Glaesserella was enhanced by external DNases and degraded NETs. This indicates that Glaesserella takes up degraded NET components, supplying them with nicotinamide adenine dinucleotide (NAD), as this benefit was diminished by inhibiting the 50 -nucleotidase, which metabolizes NAD. Our results indicate a serotype-independent interaction of Glaesserella with neutrophils by inducing NET-formation and benefiting from DNA degradation.